Suppression of acquired immunity against Listeria monocytogenes by amphotericin B$bmediated inhibition of CD8 T cell function - Geginat, Gernot; Kretschmar, Marianne; Walter, Simon; Junker, Dieter; Hof, Herbert; Nichterlein, Thomas (The journal of infectious diseases, 1999)
Amphotericin B is frequently used for the treatment of fungal infections of immunocompromised individuals. Whereas immunomodulatory side effects of this agent are known, the influence of amphotericin B was studied in the model of murine Listeria monocytogenes infection. Treatment of L. monocytogenes-immune mice with a nontoxic dose of amphotericin B (0.75 mg/kg) reduced antilisterial protection by 4-5 orders of magnitude, while it had no significant effect on natural immunity against L. monocytogenes in naive mice. Treatment of mice with amphotericin B also abolished the protection mediated by transfer of an L. monocytogenes-specific CD8 T cell line. Furthermore, in vitro analysis showed that amphotericin B impaired target cell lysis and interferon-γ production by peptide-specific CD8 T cell lines and antigen presentation by L. monocytogenes-infected macrophagelike cells. These data indicate that amphotericin B has a strong suppressive effect on the function of CD8 T cells in vitro and in vivo.